Differentiated Learning Model in Inclusive Education to Strengthen The Pancasila Students Profile - Dwikurnaningsih, Yari; Krismiyati, Krismiyati; Wardani, Krisma Widi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop a differentiated learning model in inclusive education to strengthen the Pancasila Student Profile, which can be a practical guide for teachers. The method used in this study is the design approach, which has four stages of research, namely initial research to obtain an overview of the implementation of differentiated learning, conducting literature reviews, developing model designs, validating, and testing. The subjects of this study are principals and teachers of elementary schools in Boyolali Central Java. Data collection techniques used questionnaires, interviews, and focus group discussions (FGD). The data analysis technique used in this research is descriptive analysis, combining qualitative and quantitative approaches. Based on the results of the development, the model is named the Pancasila Differentiated Learning Model, which contains model description and its syntax consisting of 5 stages; understanding the student, preparing the options, providing the options to the students, observing & supporting, and reflecting. Two experts have validated the model with good results. In addition, it has been tested on four school principals and eight elementary school teachers with excellent results. Based on the results of validation and trials, it can be concluded that the Pancasila differentiated learning model can be implemented in the school setting.Â